What is a ‘National Framework’? Some Remarks, Questions, and Considerations on an Article by Miloš Řezník - Horský, Jan (Dějiny – teorie – kritika, 2008)
This is a contribution to the discussion on Miloš Řezník’s article, ‘Národní kategorie a současná historiografi e’ (National categories and contemporary historiography), published in Dějiny – teorie – kritika 3/2006, p. 7–34. I operate nominalistically with the category of nation. In contrast to the study of history in the ‘national historical framework’ I propose the historical analysis and microhistorical correction to the macro-analytical approaches of ‘national history’ (both in principal in agreement with Řezník). Th e main part of my discussion is, however, concerned with Řezník’s argument that one cannot leave the ‘national historical framework’ without also taking up a position on national identity. My emphasis here is on Weber’s idea of ‘value neutrality’. I also point out the need to distinguish between diff erent layers: (1) (potential) national life, (2) national consciousness, (3) consciousness and a refl ected identifi cation of oneself as a member of a certain nation, and (4) the situation in which national motifs enter into the intentionality of social behaviour. These levels should not be confused when conducting research.